IMPLEMENTATION OF THE INTEGRATED NON-COMMUNICABLE DISEASES (POSBINDU PTM) â€œHOPE HEALTHâ€ PROGRAM IN KARANGSALAM VILLAGE, SUSUKAN DISTRICT, BANJARNEGARA REGENCY - Indah Ayu Sofiyanti; Taufik Purboyo; Sartono Sartono (Department of Public Administration, University Wijaykusuma Purwokerto, 2023)
This research examines the implementation of the